2015
DOI: 10.4239/wjd.v6.i3.380
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 diabetes: A predictable disease

Abstract: Type 1 diabetes (T1D) is an autoimmune disease characterized by loss of insulin producing beta cells and reliance on exogenous insulin for survival. T1D is one of the most common chronic diseases in childhood and the incidence is increasing, especially in children less than 5 years of age. In individuals with a genetic predisposition, an unidentified trigger initiates an abnormal immune response and the development of islet autoantibodies directed against proteins in insulin producing beta cells. There are cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(83 citation statements)
references
References 118 publications
0
81
0
2
Order By: Relevance
“…Despite many encouraging preclinical studies, the clinical benefits of antigen therapy in T1D have been limited, and much below expectations. It is beyond the scope of this manuscript to discuss these studies in detail, but they have been recently reviewed [76,92,98].…”
Section: Therapeutic Vaccination Against Gad65 and Insulin In T1dmentioning
confidence: 98%
See 1 more Smart Citation
“…Despite many encouraging preclinical studies, the clinical benefits of antigen therapy in T1D have been limited, and much below expectations. It is beyond the scope of this manuscript to discuss these studies in detail, but they have been recently reviewed [76,92,98].…”
Section: Therapeutic Vaccination Against Gad65 and Insulin In T1dmentioning
confidence: 98%
“…Antigens, or related peptides, have been administered by a variety of routes (subcutaneous, oral or nasal) and adjuvant formulations [76,[91][92][93][94][95][96][97][98]. Genetic (DNA) vaccination has also been investigated [99][100][101][102].…”
Section: Therapeutic Vaccination Against Gad65 and Insulin In T1dmentioning
confidence: 99%
“…In general, autoimmune diseases are characterized by specific auto-antibodies [44, 45]. However, the search for characteristic narcolepsy autoantibodies has been futile with no auto-antibodies consistently found [4660].…”
Section: Role Of Humoral Immune Responses In Narcolepsymentioning
confidence: 99%
“…In children, IAA is often the first antibody to develop, while adults tend to have higher rates of GADA upon diagnosis. 53 Through the analysis of data collected by prospective studies on the natural history of DM1 in first-degree relatives of high-risk patients with HLA haplotypes monitored from birth, it was observed that the detection of multiple autoantibodies against the islet in these children could be interpreted as a pre-clinical stage of DM1. In addition, observation within a period of 10 years after seroconversion suggests that the lower the age upon the onset of autoimmunity directed at the islet, the quicker the progression to clinical diabetes before puberty, and that the processes responsible for this phenomenon must be operating before the age of 2 years, or even during pregnancy.…”
Section: The Natural History Of Type 1 Diabetes Mellitusmentioning
confidence: 99%